Effective potentials for H2O-He and H2O-Ar systems. Isotropic induction-dispersion potentials; The European Physical Journal D; Vol. 71, iss. 5 - Starikov V. I. Vitaly Ivanovich; Petrova T. M. Tatiana; Solodov A. M. Alexander; Solodov A. A. Alexander; Deichuli V. M. Deichuli (2017, 2017)
Title screen